2022
DOI: 10.3389/fphar.2022.791922
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cytochrome P450 Enzymes in COVID-19 Pathogenesis and Therapy

Abstract: Coronavirus disease 2019 (COVID-19) has become a new public health crisis threatening the world. Dysregulated immune responses are the most striking pathophysiological features of patients with severe COVID-19, which can result in multiple-organ failure and death. The cytochrome P450 (CYP) system is the most important drug metabolizing enzyme family, which plays a significant role in the metabolism of endogenous or exogenous substances. Endogenous CYPs participate in the biosynthesis or catabolism of endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 160 publications
0
12
0
Order By: Relevance
“…Generally, CYPs’ expression or activity decrease during viral infections, chronic inflammation and in presence of proinflammatory cytokines (e.g. IL-6, TNF-α, IFN-γ TGF-β and IL-1β), which can result in alterations of the pharmacological effects of substances in inflammatory diseases (Christmas, 2015; Wang et al, 2022). Surprisingly, ORF7a and ORF7b overexpression led to significant down-regulation of genes coding for CYP enzymes such as CYP1B1, CYP2F1, CYP2T3P, CYP4F3, CYP27C1 and CYP26A1 ( Figure 4a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, CYPs’ expression or activity decrease during viral infections, chronic inflammation and in presence of proinflammatory cytokines (e.g. IL-6, TNF-α, IFN-γ TGF-β and IL-1β), which can result in alterations of the pharmacological effects of substances in inflammatory diseases (Christmas, 2015; Wang et al, 2022). Surprisingly, ORF7a and ORF7b overexpression led to significant down-regulation of genes coding for CYP enzymes such as CYP1B1, CYP2F1, CYP2T3P, CYP4F3, CYP27C1 and CYP26A1 ( Figure 4a ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we observed high expression of UGT1A1 (log2FC>4), together with some other UGT genes such as UGT1A9 ( Figure 4 ) suggesting that ORF7a and ORF7b may induce metabolic disorders which could alter the levels of bilirubin and other metabolites and may facilitate inactivation of drug therapies that could explain the inefficiency of most of the COVID-19 treatments used. Moreover, many drugs used in COVID-19 patients are metabolized by CYPs (Wang et al, 2022); therefore, if CYPs’ expression is greatly altered in COVID-19 patients, it may contribute to altered drug pharmacokinetics and increased drug-related side effects.…”
Section: Discussionmentioning
confidence: 99%
“…In case of cytokine rush, such accelerated immune response may in turn, damage the host cells. Several studies correlated the downregulation of CYP1A1 with increasing pro-inflammatory cytokines levels (IL-6, TNF-α, IL-1, IL-1β) ( Wang et al, 2022 ). In this study we speculate that CYP1A1 could be crucial in COVID-19 prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the P450 cytochrome CYP1B1 is a key factor in the regulation of redox homeostasis [ 93 ]. During hyperoxic conditions, as occurring in COVID-19, CY1B1, whose production is enhanced by TNF-α, buffers ROS by forming oxidized adducts in DNA [ 94 ]; therefore, COVID-19 is a condition where the role of CYP1B1 as a key regulator of ROS as signaling molecules is impaired, due to TNF-α. Ozone can be “sensed” by cells via the aryl hydrocarbon receptors (AhRs) [ 95 ], and AhRs-downstream signaling activates the CYP1B1 [ 96 ].…”
Section: The Role Of Ozone In the Mito-hormetic Machinerymentioning
confidence: 99%